Scientific Approaches to Human Capital Development in The Context of Digitalization of The Economy ("Journal "U". Economy. Management. Finance.", 2020)
The structure of the education system in the last decade has undergone quantitative changes associated with a decrease in the number of budgetary and commercial educational institutions. The relevance of the article lies in the need to develop human capital in the conditions of digitalization of the economy and a dynamically changing external environment. The purpose of the article is to review scientific approaches to human capital and propose a model for its development.
Keywords: human capital; development model; digitalization of the economy; educational organization